Hermeneutical postphenomenology: Computational tools and the lure of objectivity. - Farinola, Augustine (Digital Scholarship in the Humanities, 2023)
This paper examines some of the issues surrounding this 'computational turn' and proposes a 'human focused' approach. It begins by addressing questions concerning whether there is a need empirical evidence in literary studies, and the roles played by human and technical agents in interpretative practices. It adopts Don Ihde Postphenomenological ideas (especially 'embodiment' and 'hermeneutics' human-technology relations) to expatiate on the nature of relationship that exists between a literary scholar and a computational tool during interpretative practices. On one hand, it uses postphenomenomelogy as a theoretical framework to provides rich conceptual terminologies by which we could interrogate humanists-computer relationship within the practice of computational textual analysis. And on the other hand, uses postphenomenology method to highlight the notion of subjectivity in contrast to the promise of observer-independent objectivity. The research appraise the impact of quantification and visualizations in literary studies using the research output of Franco Moretti and his colleagues at the Stanford Lit Lab, as well as performs textual experimentation on some corpora using Stefan Sinclair and Geoffrey Rockwell's Voyant tools and Python NLP packages. But refutes the idea that quantification and visualization of textual data with the use of computational tools and methods could guarantee objectivity of textual interpretation in literary studies. The argument in this paper is divided across its three sections: The first section discusses the goal of reading; it concerns 'Close reading' and 'Distant reading'. The second section questions the possibility of objectivity in textual interpretation using quantifiable and visual evidence provided as the output of the computational analysis of humanistic texts. Then, in the third section defends the following claims: a) the human person is the principal actor in the interpretation process, and all other forms of representation or visualisation of the text are meant to aid humans; b. data in the humanities are not limited to printed texts, but include digitised, born-digital and electronic text in various digital forms (images, sounds, videos, etc.); c. the humanities aim more at interpretive practices than a quest for verifiable knowledge; d. interpretative practices in the humanities focus on humans and their experiences; e. attention must be drawn to human developers' subjectivity whenever we are using computational interpretative tools – on the ground that this will help in bracketing of our biases, prejudices, preconceptions, and theoretical frameworks. The paper concludes with the argument that computational tools used for textual analysis in the humanities need interpretation as they are not neutral in hermeneutic practices. It argues that the humans involved in the creation of those tools are prone to errors, have preferences, and incorporate their subjective ideas into developmental processes. Then proposes 'Hermeneutical Postphenomenology' as an ideal lens through which the claim to objectivity could be debunked. Then recommends that our productivity in textual scholarship can be enriched when we understand the true nature of the relationship between the human inquirer and technical agents within the cognitive assemblage.